IMPLEMENTATION OF LAW NOMOR 6 TAHUN 2014 ON VILLAGE AUTHORITY IN PAKKAT HAUAGONG VILLAGE HUMBANG HASUNDUTAN DISTRICT - Henny Simarmata; Tamaulina Br Sembiring (RADJA PUBLIKA, 2024)
Villages as the main milestone in the development of the State have the right of origin and traditional rights in regulating and managing the interests of local communities and play a role in realizing the ideals of independence based on the 1945 Constitution of the Republic of Indonesia, although Village Regulations are not explicitly explained in the hierarchy of legislation in Indonesia. Villages in their governance and development arrangements are regulated in Law No. 6 of 2014. This research is a descriptive qualitative research with the type of research used is Field Research. The results of this study are the implementation of the formation of village regulations in Pakkat Hauagong Village, Humbang Hasundutan Regency still has many shortcomings in the formation process. In the formation of village regulations in Pakkat Hauagong Village, there are still many inhibiting factors such as people who are still unfamiliar with village regulations, lack of cooperation between the Village Head and the Village Consultative Body (BPD) and Pakkat Hauagong Village as a village where the majority of Batak Toba people are still more dominant in using customary law than village regulations in solving problems.